Photodecomposition of Molybdenum andTungsten Carbonyl Complexes - Thamer A. Alwani; Ayad H. Jassim; Falah H. Hussein (E-Journal of Chemistry)
The photodecomposition of four different colored organometallic molybdenum and tungsten carbonyl complexes, i.e. [Mo(CO)5)2LA] (complex I), [(Mo(CO)3(bipy))2LB] (complex II), [(W(CO)3(tmen))2LB] (complex III) and [Mo(CO)2LC]2 (complex I V) where LA 2-phenyl-1,3-indandione)bis(2-methyl anilines, LB 2-phenyl-1,3-indandione) bis (4-hydroxy anilines and LCbis (2-hydroxo-benzalydine) benzidine ion have been performed at 365 nm in chloroform at 25 °C under oxygen atmosphere. The absorbance spectrum of these complexes has been recorded with the time of irradiation in order to examine the kinetics of photodecomposition. The rate of the photodecomposition process was investigated and the relative values of the rate constants of dissociation (Kd) for the first-order reaction are tabulated. The apparent rate constant of photodecomposition was found to be (8.33-11.50) × 10-5 s-1.